1967
DOI: 10.1104/pp.42.9.1176
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease Activity of Stressed Tomato Leaflets

Abstract: Siwninary. Homogenates of leaflets of desiccated tomato plants show increased ribonuclease activity compared to homogenates of turgid controls. Much of this increase is iindependent of changes in translocation to and from the leaflet. Interruption of translocation through living cel'ls by detachment of leaflets or steam damage to the petiolules prodluces increased ribonuclease activity, but this activity is increased further when excised leaflets are allowed to wilt. Increases in rihonuclease often parallel or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

1968
1968
1982
1982

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 11 publications
(5 reference statements)
1
11
0
2
Order By: Relevance
“…Since no change in RNase activity was seen in the control during the 3-hr experiment, the increase in RNase during desiccation appeared to be due to the decrease in T, and not to excision. Similar increases in RNase activity have been reported as a result of inadequate water supply (7,22). Tvorus (22) has indicated that the increase probably is due to de novo synthesis of the enzyme, since the response to desiccation could be prevented by cycloheximide.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Since no change in RNase activity was seen in the control during the 3-hr experiment, the increase in RNase during desiccation appeared to be due to the decrease in T, and not to excision. Similar increases in RNase activity have been reported as a result of inadequate water supply (7,22). Tvorus (22) has indicated that the increase probably is due to de novo synthesis of the enzyme, since the response to desiccation could be prevented by cycloheximide.…”
Section: Resultssupporting
confidence: 60%
“…Among the activity of certain enzymes (1,12,7,22). One of the most severely affected is nitrate reductase which has been shown to decline to 42% of the controls in barley leaves having a T"' of about -11 bars (12) and to 50% of the controls in corn seedlings having a water deficit of 10% (1).…”
mentioning
confidence: 99%
“…Prolonged and severe water stress increases the ribonuclease level in plants (6). The possibility existed that the reduction in polysomes in stressed tissue was an artifact caused by increased ribonuclease activity during isolation.…”
Section: Resultsmentioning
confidence: 99%
“…An increase of RNase activity (1,6,7,9,12,35) and a decrease of RNA level (8,12) was found in tomato and other plants subjected to water stress. The soluble fraction of RNA increased while the ribosomal fraction decreased in sugar beet under water stress (25).…”
Section: Introductionmentioning
confidence: 97%